First Mile program: North-South partnership experience with health system strengthening in Mbarara, Uganda - Olds, Peter K.; Asiimwe, Stephen; Kembabazi ,Annet; Ainomugisha, Andrew; Jodi Ansel, Moses; Joseph Ngonzi; Grace Nambozi; Mugema Mulogo, Edgar; Ntaro , Moses; Data, Santorino; Atwine, Raymond; Obunguloch, Johnes; et al. (Global Health Action, 2026)
Uganda’s public healthcare system faces significant systemic challenges in delivering care, contributing to poor health outcomes. In response, a North-South partnership between Massachusetts General Hospital (MGH), Mbarara University of Science and Technology (MUST), and Mbarara Regional Referral Hospital (MRRH) implemented the First Mile Project, a seven-year initiative (2018–2024) designed to strengthen the regional health system in southwestern Uganda. Guided by local priorities, the program aimed to improve access to care, enhance clinical capacity, expand medical education, and promote research and innovation. Project activities were devised collaboratively between investigators at MGH and MUST/MRRH, with robust local leadership and oversight. Key initiatives included clinical staffing in critical departments, construction of a regional isolation ward and oxygen plant. Additionally, the program provided scholarships for medical training, support for community-based care and continuing medical education, and provision of research and innovation grants. The program trained over 1500 health workers, supported 93 scholarships, increased access to specialized clinical services, and facilitated community outreach to thousands of households. The project also awarded 74 research grants and supported over 30 locally incubated innovations. Through this comprehensive, equity focused approach, First Mile demonstrated how collaborative, locally driven partnerships can effectively strengthen health systems in low-resource settings. Lessons from the initiative underscore the importance of sustained local leadership and integrated clinical and research efforts. A 20-year history of collaboration and mutual trust ensured open dialogue between partners and helped support the success of the project. The First Mile model provides a promising example for future health system strengthening initiatives globally
Keywords: collaborations; capacity building; equity; clinical care delivery; clinical education; research and innovation support